Remarks at Thomson Reuters Newsmaker Event, London, U.K., June 19, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses climate change as being a fundamental threat to economic development and the fight against poverty. He releases the new climate change report “Climate Extremes: Regional Impacts and the Case for Resilience” which talks about the challenges we’d be facing if the global temperature rose by two degrees Celsius. He talks about developing tools that help countries better assess and adapt to climate change, including greenhouse gas emissions tracking, helping countries become more energy-efficient, and advising them on building more climate-resilient infrastructure. He speaks about working with partners on building low-carbon climate-resilient cities, transforming the way to maximize productivity and resilience and doubling global renewable energy and efficiency. In conclusion, he says that the world needs to find innovative ways to set an appropriate price on carbon and roll back fossil fuel subsidies. He fielded questions on the U.N. climate policy process, corruption in lending to Africa, the role of China in slowing emissions, the role of bilateral agreements, getting youth involved, energy efficiency in the United States, and barriers to investment in low carbon industries.